Helical reconstruction of Mycobacterium smegmatis Mycothiol S-conjugate amidase filaments - Burgess, Jeremy Gareth (Division of Medical Biochemistry and Structural Biology, 2017)
The metabolic pathway of mycothiol (MSH) is a major cellular defence against oxidative stress, and several antibiotics for mycobacteria, including Mycobacterium tuberculosis. The central enzyme used in the clearance of electrophilic toxins is Mycothiol S-conjugate amidase (Mca). Mca is similar to a biosynthetic enzyme MshB, which has partial overlapping substrate activity and is the closest homologue to Mca with a known structure. The basis for the substrate specificity differences in Mca and MshB is not well understood. Several regions of low sequence similarity between MshB and Mca are contained within an active site pocket, and these may affect the observed substrate preferences. However, these regions cannot be modelled in Mca with confidence, which makes it essential to obtain a structure of Mca experimentally. Mca is also a potential drug target, and a structure of Mca would enhance the rational design of inhibitors against the enzyme. A search for crystalline forms of MsMca (Mycobacterium smegmatis Mca) led to the discovery of regular filaments, which showed helical order. Helical symmetry was estimated using power spectra from single filaments. The number of potential symmetry solutions was reduced using phase information from Fourier transforms of single filaments. Three possible solutions to the helical symmetry were suggested, two of which converged on the same symmetry parameters using Iterative Helical Real-Space Reconstruction. The first solution had a selection rule of l = 18m + n, and the second l = 20m + n. Reconstructions made from the predicted helical symmetries were compared in their power spectra and through rigid-body fitting with an atomic model of MsMca. The first reconstruction, with a final symmetry of Δφ = 20.05o and Δz = 10.27 Å, better matched the predicted helical symmetry than did the second reconstruction. However, rigid-body fitting did not indicate either reconstruction as being superior. Following this, the second reconstruction was improved using a number of additional techniques to those used in the initial reconstruction. These included the use of the fortuitous 3-fold cyclic symmetry, the removal of double-walled filaments, use of a cut-off filter for images with low correlation to projections of the 3D reconstruction, and use of a layer-line filter to reduce the noise in the images. These were used individually, then in a single reconstruction, to improve the and agreement between the predicted helical symmetry and that obtained from the reconstruction. Several of the improved reconstructions were used via rigid-body fitting to assess the favoured handedness of the filament through examination of the major interfaces between subunits. These suggest that the 3-start helix is right-handed. Future work would be to determine the handedness of the filament using alternative techniques, such as metal-shadowing. This work provides a springboard for high resolution cryo-electron microscopy, to determine a high-resolution structure of MsMca, which will enable rational inhibitor design and give the basis for the different substrate specificity in Mca and MshB.